2019
DOI: 10.1186/s13568-019-0747-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with fermented Mao-tai lees beneficially affects gut microbiota structure and function in pigs

Abstract: Gut microbiota positively contribute to livestock nutrition and metabolism. The manipulation of these microbes may improve animal health. Some feed additives improve livestock health and metabolism by regulating gut microbiota composition and activity. We fed hybrid pigs diets supplemented with 0% (control), 5% (treat 1), 10% (treat 2), or 15% (treat 3) fermented Mao-tai lees (FML) for 90 days. Short-chain fatty acids (SCFAs), bioamines, and microbial communities found in colonic contents were analyzed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Roseburia, SCFA producers, acidifies the intestinal environment, thus conducive to the growth of beneficial bacteria and inhibits the proliferation of harmful bacteria (66,67). Like our study, Roseburia was also enriched in the 15% fermented Mao-tai lees group (68). Moreover, the abundance of E. coli decreased after feeding an FSMS diet.…”
Section: Microbial Communitysupporting
confidence: 74%
“…Roseburia, SCFA producers, acidifies the intestinal environment, thus conducive to the growth of beneficial bacteria and inhibits the proliferation of harmful bacteria (66,67). Like our study, Roseburia was also enriched in the 15% fermented Mao-tai lees group (68). Moreover, the abundance of E. coli decreased after feeding an FSMS diet.…”
Section: Microbial Communitysupporting
confidence: 74%
“…In the present study, dietary 2–6% FML supplementation had no significant effect on the abundances of Clostridium clusters IV and Lactobacillus of the weaned pigs. However, our previous studies showed that dietary 15% FML supplementation could increase the abundance of Lactobacillus of the growing-finishing pigs ( Li et al, 2019 ). This discrepancy might be related to the different doses of FML supplementation and the age of pigs.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies also confirmed that dietary 15% FML supplementation could decrease the abundance of potential pathogen Escherichia spp. in pigs at different ages ( Li et al, 2019 ). These findings suggested that dietary FML supplementation, particularly 4% FML, could regulate the balance of intestinal microflora.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations